Higher Nutritional Status of Lung Cancer Cachexia Patients is Associated with Higher Functional Capacity and Appetite - Diana Sunardi; Saptawati Bardosono (World Nutrition Journal, 2019)
Introduction: Lung cancer is highly prevalent and the major cause of cancer-related deaths worldwide.  Severity of weight loss has been shown to have a negative impact on patients’ performance and quality of life.  Early detection of anorexia and decline of functional capacity will be very usefull to prevent severe weight loss and a better prognosis. Methods: A cross sectional study was conducted in Dharmais Cancer Hospital.  Subjects were lung cancer patients newly diagnosed or a minimal of 2 months pasca chemotherapy or radiotherapy, taken consecutively from inpatients and outpatients.  Results: Subjects eligible for the study were 47, with a composition of 55.3% men and 44.7% women in the age range from 36–79 years old. There were significant relationship between body weight and BMI with ECOG score. Body weight, BMI  and weight loss related significantly with VAS appetite and SNAQ score.  These result indicate that subjects with a higher BMI and a lower weight loss have a better physical performa and appetite.  There were significant relation between haemoglobin level, anemia status and serum albumin level with appetite and risk for anorexia. This result indicate that subjects with normal haemoglobin  and albumin have a good appetite and a lower risk for anorexia.  Conclusions: Positive prognosis of cancer patients can be obtained by maintaining BMI and preventing weight loss, since both affected the already known prognostic marker functional capacity significantly.  Serum Albumin and hemoglobin are not only simple test, but also brings benefits, a clinical marker that may be used to assess the risk of anorexia.